2019
DOI: 10.29252/ijcp-25263
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Profile Parameters and Coronary Artery Disease in Young Patients Undergoing Diagnostic Angiography

Abstract: Introduction: It is vital to understand the association between lipid profile and the severity of coronary artery disease (CAD) in young patients with suspected CAD. The clinical presentation, lipid profile and severity of CAD may differ in patients who develop CAD at young age and those at older age. Friesinger (FR) index is an important tool to assess the extent and severity of coronary artery lesions. Methods: This study was a single center retrospective study involving patients below 40 years who underwent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Few small studies have investigated association between conduction disturbance & coronary atherosclerosis. 2 , 3 , 4 , 5 , 6 These studies showed 15–70% association of chronic coronary artery disease in chronic conduction disorders. 7 , 8 , 9 , 10 Coexistence of CAD with symptomatic bradycardia has major effects on prognosis & long term plan of care in form of either medication or revascularization.…”
Section: Introductionmentioning
confidence: 96%
“…Few small studies have investigated association between conduction disturbance & coronary atherosclerosis. 2 , 3 , 4 , 5 , 6 These studies showed 15–70% association of chronic coronary artery disease in chronic conduction disorders. 7 , 8 , 9 , 10 Coexistence of CAD with symptomatic bradycardia has major effects on prognosis & long term plan of care in form of either medication or revascularization.…”
Section: Introductionmentioning
confidence: 96%